A comparative analysis of carcass traits and meat quality between Tibetan sheep and their three-way crossbred sheep - Qiao, Yu; Yang, Deming; Tang, Jishun; Zhang, Wei; Chen, Sheng; Hui, Wenqiao (Frontiers in Nutrition, 2025)
IntroductionTo improve meat yield and nutritional quality of Tibetan sheep of the Qinghai-Tibet Plateau, Australian White and Small-tailed Han rams were introduced to crossbred with Tibetan sheep (Oura-type, O) ewes which possessed genetic homogeneity. The aim of this study was to compare growth conformation, meat quality, and further identified related candidate genes between Tibetan sheep and their three-way crossbreds (25% Australian White × 25% Small-tailed Han × 50% Oura-type Tibetan, AHO).MethodsFifteen 5.5-month-old male lambs (8 O and 7 AHO crossbred) were raised for 5.5 months. We compared body conformation, carcass traits, meat quality (pH, color, cooking loss), nutrient composition (amino acids, fatty acids, ribonucleotides) in longissimus thoracis et lumborum (LTL) muscle, and analyzed differentially expressed genes through transcriptomics.ResultsOur findings indicated that 5.5-month-old AHO lambs exhibited significantly superior body conformation and carcass traits (p < 0.05), including live weight, cannon circumference, carcass weight, and loin eye area. Their LTL muscle contained higher levels of PUFA, n-6 PUFA, and a greater PUFA/SFA ratio along with the content of glutamic acid and methionine (p < 0.05), and an increased trend for inosine monophosphate (p = 0.072) in the AHO lambs than O groups. Transcriptomic analysis identified candidate genes including CSRP3, ANKRD1, IFRD1, PPARGC1A, and AMPD3, which are differentially expressed and associated with muscle development and meat flavor.ConclusionThe study revealed that AHO lambs demonstrated better growth and meat quality, with identified candidate genes for these traits. These findings provide practical strategies for enhancing Tibetan lamb meat quality through crossbreeding optimization in high-altitude regions.